Hubungan kadar leptin plasma, lipid plasma, dan waist to hip ratio dengan kejadian stroke - Suherman A. Tambunan; Yuneldi Anwar; Hasan Sjahrir (Majalah Kedokteran Nusantara The Journal Of Medical School, 2014)
Background : Stroke constitutes a national health problem with many risk factor. Leptin, produced by adipocyte was shown to be important risk factor for stroke. The circulating lipids and lipoproteins plays an important etiologic role in stroke. Waist to hip ratio (WHR) has been shown to be predictor of stroke. The purpose of this study is to investigate the correlation between plasma leptin, plasma lipid and WHR with stroke.Methods : A cross-sectional study performed in stroke and non stroke matched patients in Adam Malik General Hospital from March until June 2012. Concentration of plasma leptin, plasma lipid and WHR was examined and then performed a statistical analyzed.Results : From 62 subjects with stroke and non stroke have a significant correlation between plasma leptin with stroke in female group (p=0.036), but not in male (p=0.454), a significant correlation between HDL (p=0.000) and triglyceride (p=0.000) with stroke, no significant correlation between WHR and stroke in male (p=0.776), significant correlation between waist circumferences (p=0.005) and hip circumferences (p=0.002) with stroke in male. There was moderate correlation between plasma leptin and total cholesterol in stroke (r=0.413), weak correlation between plasma leptin and LDL in stroke (r=0.392), moderate correlation between plasma leptin and waist circumferences in stroke (r=0.505), strong correlation between plasma leptin and hip circumferences in stroke (r=0.624). No significant correlation between plasma leptin (p= 0.937), plasma lipid and WHR in stroke Conclusion : There was significant correlation between plasma leptin and stroke in female group, significant correlation between HDL and triglyceride with stroke, significant correlation between total cholesterol and LDL with plasma leptin in stroke. Keywords : stroke; plasma leptin; plasma lipid; WHR.